Phytochemical Investigation and Anti Microbial and Enzyme Inhibition Activity of Murraya Koenigii (Linn).Spreng - MUTHUMANI, P (International Journal of Pharmaceutical & Biological Archive, 2010)
To investigate the antibacterial and antifungal activity of insolated compounds by column chromatography obtained from Murraya Koenigii stem bark extracts. The isolated compounds of Murraya Koenigii (Su-I, Su-II, Su-III and Su-IV) were tested for antibacterial efficacy against staphylococuus aureus and antifungal efficacy against candida albicans. The antimicrobial effect produced by the isolated compounds was comparable to that of Amikacin and Griseofulvin. The isolated compounds (Su-II, Su-III and Su-IV) were found out in amylase and urease enzyme. The isolated compounds (Su-III and Su-IV) showed high enzyme inhibitory activity.